Influence of Bicycle Deformation and Type on Head Injury Values of a Cyclist in a Car-to-Bicycle Collision - Ryo Nakahara; Yuto Suzuki; Nana Takeuchi; Toshiaki Sakurai; Tetsuo Maki; Iwao Imaizumi; Hisaki Sugaya; Yukou Takahashi; Yasuaki Gunji (International Journal of Automotive Engineering, 2019)
In this study, finite element models for two types of bicycles with different shapes were constructed. These deformable models were validated in quasi-static loading conditions, and were used to investigate the effect of the deformation of the bicycle body on the head injuries to its occupant. The analysis confirmed that, when deformable models are used, the kinematics of the cyclist after the contact with a vehicle changes, and the injury values are different, from those obtained by rigid models. In addition, different bicycle types produce different riding postures, which significantly change the rotational motion of the cyclist around the vertical axis, subsequently affecting head injuries.